PENGEMBANGAN PENILAIAN KSAO UNTUK PERUSAHAAN PIALANG ASURANSI DI INDONESIA - Pakpahan, Giselle Abrian (Jurnal Administrasi Bisnis, 2023)
In an industry that is engaged in the sale of services, individuals who carry out these service activities are the determining factor for company performance. Therefore, it is necessary to have human resources who meet the qualifications in order to meet the specified targets and maintain consistency of service quality. This phenomenon is clearly seen in the Insurance Brokerage industry, where in 2016 the Indonesian government introduced a regulation that regulates the minimum qualification requirements for Insurance Brokers to operate. The purpose of this research is to create a position profile and assessment of KSAO to help set standards when recruiting and selecting insurance brokers. In forming a position profile using the theory of recruitment and selection based on competence according to Dubois et al (2004) that supported by KSAO model according to Krumma, et all (2016). This research is a qualitative research using case study method. The data collection technique used is interviews supported with secondary data both provided by the company and documents outside the relevant company internal data. The results of the research are to form a position profile and assessment of the Insurance Broker position which is used as the basis for recruitment and selection.